Influence of flue gas recirculation on the performance of incinerator-waste heat boiler and NOx emission in a 500 t/d waste-to-energy plant - Liu, Jun (Waste management (New York, N.Y.), 2020)
Copyright © 2020 Elsevier Ltd. All rights reserved.